Italian consensus conference on guidelines for conservative treatment on lower limb muscle injuries in athlete. Issue 1 (24th May 2018) - Bisciotti, Gian Nicola; Volpi, Piero; Amato, Maurizio; Alberti, Giampietro; Allegra, Francesco; Aprato, Alessandro; Artina, Matteo; Auci, Alessio; Bait, Corrado; Bastieri, Gian Matteo; Balzarini, Luca; Belli, Andrea; et al.
Abstract : Provide the state of the art concerning (1) biology and aetiology, (2) classification, (3) clinical assessment and (4) conservative treatment of lower limb muscle injuries (MI) in athletes. Seventy international experts with different medical backgrounds participated in the consensus conference. They discussed and approved a consensus composed of four sections which are presented in these documents. This paper represents a synthesis of the consensus conference, the following four sections are discussed: (i) The biology and aetiology of MIs. A definition of MI was formulated and some key points concerning physiology and pathogenesis of MIs were discussed. (ii) The MI classification. A classification of MIs was proposed. (iii) The MI clinical assessment, in which were discussed anamnesis, inspection and clinical examination and are provided the relative guidelines. (iv) The MI conservative treatment, in which are provided the guidelines for conservative treatment based on the severity of the lesion. Furthermore, instrumental therapy and pharmacological treatment were discussed. Knowledge of the aetiology and biology of MIs is an essential prerequisite in order to plan and conduct a rehabilitation plan. Another important aspect is the use of a rational MI classification on prognostic values. We propose a classification based on radiological investigations performed by ultrasonography and MRI strongly linked to prognostic factors. Furthermore, the consensus conference results will able to provide fundamental guidelines for diagnostic and rehabilitation practice, also considering instrumental therapy and pharmacological treatment of MI. Expert opinion, level IV.